Role of pretreatment neutophil to lymphocyte ratio as an independent prognostic factor in oral squamous cell carcinoma patients: a prospective study in a tertiary care centre - Tiwari, Shashwat; Nautiyal, Shivani (International Journal of Research in Medical Sciences, 2018)
Background: More recently, established systemic inflammation-based prognostic scores have been explored extensively, such as NLR and serum C-reactive protein (CRP). We postulated that NLR might be a readily available and inexpensive objective prognostic index that could be used in daily oncologic clinical practice and could help to stratify patients in clinical trials. Methods: In total, there were 150 patients with OSCC treated at GSVM medical college, Kanpur between October 2012 and January 2015 whose clinical information and laboratory parameters were obtained. The NLR was determined by dividing the absolute neutrophil count by the absolute lymphocyte count, and the NLR data were then dichotomized and divided into two groups as NLR-low and -high. Results: The 3-year OS rate of the NLR-high group tended to be significantly lower than that of the NLR-low group, this relationship was found to be statistically significant (p value <0.05). The 3-year DFS rate in the NLR-high group was lower than that in the NLR-low group; however, there were no significant difference between the two groups. Conclusions: Our findings reported herein demonstrated that pre-treatment NLR is a potential biomarker for predicting the overall survival in oral SCC patients. Combined with other markers, NLR may be used in decision-making and the selection of treatment modality in patients with oral SCC.